Ghrelin receptor antagonism of fentanyl-induced conditioned place preference, intravenous self-administration, and dopamine release in the nucleus accumbens in rats - Sustkova-Fiserova, Magdalena; Puskina, Nina; Havlickova, Tereza; Lapka, Marek; Syslova, Kamila; Pohorala, Veronika; Charalambous, Chrysostomos (Addiction biology, 2020)
The extended occurrence of fentanils abuse associated with the dramatic increase in opioid fatal overdoses and dependence strongly emphasizes insufficiencies in opioid addiction treatment. Recently, the growth hormone secretagogue receptor (GHS-R1A) antagonism was proposed as a promising mechanism for drug addiction therapy. However, the role of GHS-R1A and its endogenous ligand ghrelin in opioid abuse is still unclear. Therefore, the aim of our study was to clarify whether the GHS-R1A antagonist JMV2959 could reduce the fentanyl-induced conditioned place preference (CPP), the fentanyl intravenous self-administration (IVSA), and the tendency to relapse, but also whether JMV2959 could significantly influence the fentanyl-induced dopamine efflux in the nucleus accumbens (NAC) in rats, that importantly participates in opioids' reinforcing effects. Following an ongoing fentanyl self-administration, JMV2959 3 mg/kg was administered intraperitoneally 20 minutes before three consequent daily 360-minute IVSA sessions under a fixed ratio FR1, which significantly reduced the number of active lever-pressing, the number of infusions, and the fentanyl intake. Pretreatment with JMV2959 also reduced the fentanyl-seeking/relapse-like behaviour tested in rats on the 12th day of the forced abstinence period. Pretreatment with JMV2959 significantly and dose-dependently reduced the manifestation of fentanyl-CPP. The fentanyl-CPP development was reduced after the simultaneous administration of JMV2959 with fentanyl during conditioning. The JMV2959 significantly reduced the accumbens dopamine release induced by subcutaneous and intravenous fentanyl. Simultaneously, it affected the concentration of byproducts associated with dopamine metabolism in the NAC. Our findings suggest that GHS-R1A importantly participates in the rewarding/reinforcing effects of fentanyl.
Keywords: Triazoles; dopamin; Glycine; Self Administration; Rats; Narcotics; ghrelin antagonism; receptory ghrelinu; autoaplikace; fentanyl; Administration, Intravenous; Fentanyl; Rats, Wistar; mužské pohlaví; IVSA; krysa rodu Rattus; addiction, CPP; intravenózní podání; zvířata; triazoly; nucleus accumbens; Dopamine; Nucleus Accumbens; Receptors, Ghrelin; ghrelin; operantní podmiňování; glycin; potkani Wistar; narkotika; dopamine; Conditioning, Operant; Ghrelin; Male; Animals